Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1108/pr-09-2016-0252
|View full text |Cite
|
Sign up to set email alerts
|

Strategic flexibility, innovative HR practices, and firm performance

Abstract: Purpose-The purpose of this paper is to examine the role of innovative HR practices as an important mechanism through which strategic flexibility affects firm performance as well as the role of female leadership in this relationship. Design/methodology/approach-Data were gathered from a sample of 113 firms in China. The authors collected information on organizational strategy, HR practices, CEO information, corporate social responsibility and other firm characteristics in terms of firm age, location, and finan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
68
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(104 citation statements)
references
References 85 publications
11
68
1
1
Order By: Relevance
“…Regarding the effect of safety culture, the findings are supported by Rechenthin (2004) and Fernández-Muñiz et al (2009). Meanwhile, the effect of human resource management practices on productivity was confirmed by Pahos and Galanaki (2018) and Xiu et al (2017) and the effect of safety culture on productivity is confirmed by Lamm et al (2007) and Tappura et al (2015). The results of this study suggest several important implications for competitive advantage in the construction industry in Indonesia.…”
Section: Managerial Implications and Conclusionsupporting
confidence: 64%
“…Regarding the effect of safety culture, the findings are supported by Rechenthin (2004) and Fernández-Muñiz et al (2009). Meanwhile, the effect of human resource management practices on productivity was confirmed by Pahos and Galanaki (2018) and Xiu et al (2017) and the effect of safety culture on productivity is confirmed by Lamm et al (2007) and Tappura et al (2015). The results of this study suggest several important implications for competitive advantage in the construction industry in Indonesia.…”
Section: Managerial Implications and Conclusionsupporting
confidence: 64%
“…The nature of talent was a key factor contributing to the introduction of more extensive HRM with a positive impact found for a more highly skilled workforce (Bacon & Hoque, 2005; Barrett & Meyer, 2010; Wu, Bacon, & Hoque, 2014). Similarly, research finds support for strategy as a determinant of HR practices including TQM (Gil‐Marques & Moreno‐Luzon, 2013), entrepreneurial orientation (Messersmith & Wales, 2011), and strategic flexibility (Xiu et al, 2017), although as discussed previously the relationship between growth and HRM is less clear (de Kok & Uhlaner, 2001). Further variants included consideration of HR in the implementation of strategy including TQM (Chandler & McEvoy, 2000) and the human capital emphasis of strategy (Barrett & Meyer, 2010).…”
Section: Findings: What Do We Know?mentioning
confidence: 92%
“…Research frequently controls for internal and/or external contextual variables (Tocher & Rutherford, 2009;Xiu et al, 2017), which conceals significant contextual influence (Johns, 2006). Only 11% of studies sought to provide explanation for HRM effects through consideration of mediators which included human capital, motivation, and employee voice The 24 qualitative studies generally utilized a case study approach with interviews as the main data collection tools, with the exception of two studies, one of which used structured interviews (Heilmann,…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations